SM 01-2341 Darpi: iterative learning ecosystems in injury prevention practice. (November 2018) - Marr, Angela
Abstract : DARPI at CDC's Injury Center seeks to actively catalyze systems change, as well as the translation and implementation of effective prevention strategies, to produce rapid, equitable, and sustainable reductions in injury and violence across communities. DARPI is not limited to one particular area of injury and violence prevention. As the Injury Center's 'cross-cutting' Division, DARPI seeks to identify shared risk factors across topics and common contextual and operational themes that directly and indirectly affect the real-world success of evidence/practice-based interventions. Within the Practice Integration and Evaluation Branch we utilize an iterative learning process where research informs practice and practice informs research. New products and tools like the R2P Toolkit and the Shared Risk and Protective Factor Toolkit are driving connections in the research-2-practice-2-reseach cycle and establishing metrics for evaluating the impact of shared risk and protective factor IVP strategies. DARPI applies a CQI philosophy – focusing on value to stakeholders and two-way communication to ground action; accelerating improvements through incremental implementation/pilots and feedback to identify best practices; and building off what is learned by others and ourselves. We will explore how this iterative learning ecosystem is advancing our work with practitioners and researchers and driving population level change.